The annals of America (Chicago, 2003)
This encyclopedic set is ideal for home scholars, or as a support for an AP history program . It contains a vast storehouse of primary documents to support a deeper more personal understanding of American history including such seminal documents as George Washington's farewell address, and other key moments in American History. These volumes only for the more through researchers, since the basic descriptions of the events would be better covered by the encyclopia. many of the Photos are of the same as in Encyclopedia Britannica.
Keywords: Hoa Kỳ; Lịch sử